Repetitive Transcranial Magnetic Stimulation in Youth With Treatment Resistant Major Depression - MacMaster, Frank P.; Croarkin, Paul E.; Wilkes, T. Christopher; McLellan, Quinn; Langevin, Lisa Marie; Jaworska, Natalia; Swansburg, Rose M.; Jasaui, Yamile; Zewdie, Ephrem; Ciechanski, Patrick; Kirton, Adam (Frontiers in Psychiatry, 2019)
Background: Major depressive disorder (MDD) is common in youth and treatment options are limited. We evaluated the effectiveness and safety of repetitive transcranial magnetic stimulation (rTMS) in adolescents and transitional aged youth with treatment resistant MDD. Methods: Thirty-two outpatients with moderate to severe, treatment-resistant MDD, aged 13 – 21 years underwent a three-week, open-label, single center trial of rTMS (ClinicalTrials.gov identifier NCT01731678). rTMS was applied to the left dorsolateral prefrontal cortex (DLPFC) using neuronavigation and administered for 15 consecutive weekdays (120% rest motor threshold; 40 pulses over 4 seconds [10 Hz]; inter-train interval, 26 seconds; 75 trains; 3000 pulses). The primary outcome measure was change in the Hamilton Depression Rating Scale (Ham-D). Treatment response was defined as a greater than 50% reduction in Ham-D scores. Safety and tolerability were also examined. Results: rTMS was effective in reducing MDD symptom severity (t = 8.94, df = 31, p < 0.00001). We observed 18 (56%) responders ( 50% reduction in Ham-D score) and 14 non-responders to rTMS. Fourteen subjects (44%) achieved remission (Ham-D score ≤ 7 post-rTMS). There were no serious adverse events (i.e. seizures). Mild to moderate, self-limiting headaches (19%) and mild neck pain (16%) were reported. Participants ranked rTMS as highly tolerable. The retention rate was 91% and compliance rate (completing all study events) was 99%. Conclusions: Our single center, open trial suggests that rTMS is a safe and effective treatment for youth with treatment resistant MDD. Larger randomized controlled trials are needed.